EVALUASI PROGRAM BIMBINGAN KELOMPOK DI SEKOLAH MENENGAH ATAS NEGERI 6 MALANG: MODEL KESENJANGAN - Da Costa, Augusto (JURNAL FOKUS KONSELING, 2016)
This study aims to determine the discrepancy between the performance of group guidance program on SMA Negeri 6 Malang with standards. This study uses a standard of Guidelines for Performance Based Professional School Counselor Evaluation. Standard reads, âthe professional school counselor teaches guidance units effectivelyâ. This study is an evaluation research using a discrepancy model. Based on the data analysis of evaluation of group guidance program in SMA Negeri 6 Malang is meet the standards.Keyword: program evaluation, group guidance, discrepancy model